Orating the News: Printed Diplomatic Orations, Political Communication, and the Roots of Public Diplomacy in Renaissance Italy, 1470–1513 - O’Connell, Monique (The sixteenth century journal, 2022)
This article argues that the pressures of war at the turn of the sixteenth century converted some diplomatic orations from ritual embellishments into tools for communication to a reading public interested in news about ambassadors and their activities. Using a survey of diplomatic orations printed between 1470 and 1513, the article demonstrates that diplomats could use orations to influence public perceptions. After the 1494 French invasion of Italy, increased public interest in contemporary diplomatic news created potential audiences for printed diplomatic orations. In three case studies of orations printed in 1509/10, Jacopo Antiquario, Louis Hélian, and a speaker purporting to be Antonio Giustinian used rhetorical exaggeration to outright disinformation in order to manipulate popular perceptions against Venice. The transformation of some diplomatic orations into print aimed at persuading a reading public points to a reciprocal relationship between the evolution of print culture and diplomacy in early sixteenth-century Italy.